2020
DOI: 10.1659/mrd-journal-d-20-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Potential Distribution Patterns of Alpine Vegetation in the Hengduan Mountains Region, China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
4
3
0
Order By: Relevance
“…(see Figure 1a), while their lower limits become unsuitable for them. The prediction that highland species expand their distribution areas (Figure 3) is in line with the findings of other studies in the Himalayas (Anderson et al, 2020; He et al, 2019, 2020; Yan & Tang, 2019) and in alpine ecosystems in general (Rew et al, 2020). This suggests that warming is likely to make a large area of intermountain valleys and highland plateaus situated around 4500 m a.s.l.…”
Section: Discussionsupporting
confidence: 91%
“…(see Figure 1a), while their lower limits become unsuitable for them. The prediction that highland species expand their distribution areas (Figure 3) is in line with the findings of other studies in the Himalayas (Anderson et al, 2020; He et al, 2019, 2020; Yan & Tang, 2019) and in alpine ecosystems in general (Rew et al, 2020). This suggests that warming is likely to make a large area of intermountain valleys and highland plateaus situated around 4500 m a.s.l.…”
Section: Discussionsupporting
confidence: 91%
“…The increase of annual precipitation is also unfavorable for vegetation growth. This is consistent with the conclusion drawn by He when they studied the relationship between precipitation and vegetation ecosystem in Yunnan [34].…”
Section: Influence Of Vegetation and Meteorological Factors On Hchosupporting
confidence: 92%
“…Although the species-suitable area will be limited to higher altitudes, it is observed to be restricted to the elevation threshold of the actual species range. Those results are in accordance with the work of He et al [63], who predicted that suitable areas for alpine vegetation will shift from the lowest and highest elevations and be limited to a suitable range between 4500 and 5000 m. Moreover, Jiang et al [56] found that the future potential distribution of three Fritillaria species will shift towards higher altitudes without exceeding the actual optimum elevation range of the species. The Montpellier Maple suitable area is predicted to lose more than 99% of its value, decreasing from 4.76% to 0.05% of the total study area under the RCP 8.5 scenario for the 2060-2080 time period.…”
Section: Suitability Distribution In the Futuresupporting
confidence: 90%